(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Tax evasion is aterm whch means illegaly avoiding paying taxes by people. This illegal practice is a seriosus problem of Polish Public Authorities. There can be plenty of tax evasion reasons, for instance: economic, social and legal. Tax evasion has got anegative influence to budget. It is very important that the public authorities should conduct effective audit activities.